Effect of Irrigation Interval and Corn (Zea mays L.)-Sorghum (Sorghum bicolor L.) Intercropping on the Quantitative and Qualitative Characteristics of Fodder - Saeed Sadeghzadeh Hemayati; Hamed Mansouri; Mohsen Shahsavarpour (بوم شناسی کشاورزی)
IntroductionIran is located in the arid and semi-arid region of the world and is considered one of the low rainfall regions of the world (Khatami et al., 2020). The agricultural sector is considered to be the major water consumer, therefore paying attention to the optimal use of water in this sector is of great importance and any saving in this sector is considered an effective contribution to saving water resources (Khajeh Khezri et al., 2018). Selection of suitable cultivation patterns and systems is one of the useful solutions in the optimal use of production resources, including water. In agricultural systems with limited resources, the use of intercropping is of particular importance. It has been reported that between 16 and 22 percent of the production of the agricultural sector in the world is supplied through various intercropping systems (Chamkhi et al., 2022). Many studies have been done regarding the intercropping of two C4 fodder plants in the investigation of their performance under mixed cultivation conditions. The value of LER in corn (Zea mays L.) – sorghum (Sorghum bicolor L.) intercropping under normal irrigation and moisture stress conditions was reported as 1.35 and 1.62 respectively, which indicated the superiority of corn and sorghum intercropping over the monoculture of both plants, especially under stress conditions. In all countries of the world - especially in Iran - research and progress in fodder production, management and exploitation of these plants have received less attention than other plants. This experiment was carried out with the aim of evaluating the quantitative and qualitative performance of two types of forage corn and sorghum in the intercropping system and the responses of these plants to different levels of drought stress.Materials and MethodsThe experiment was carried out as strip plots based on randomized complete block design with three replications in Hasharabad village, Regan city, Kerman province. In this experiment, the irrigation regimes with three levels were considered as a vertical plot and different proportions of corn and sorghum mixture with five levels as a horizontal plot. The vertical plot includes three levels of irrigation as 100 mm of evaporation from the class A evaporation pan (control), 175 mm of evaporation from the class A evaporation pan (mild stress) and 250 mm of evaporation from the class A evaporation pan (severe stress). The horizontal plot also has five levels of different proportions of fodder corn and sorghum, including monoculture of corn (M), intercropping of three quarters of corn + one quarter of sorghum (3M:1S), one half of corn + one half of sorghum (2M:2S), one quarter of corn + three quarters of sorghum (1M:3S) and monoculture sorghum (S). Quality characteristics included Dry Matter Digestibility (DMD), Water Soluble Carbohydrates (WSC), Crude Protein (CP), Acid Detergent Fiber (ADF), Total ASH and Crude Fiber (CF) were measured and analysis. In order to calculate the benefits of intercropping, the evaluation indicators of intercropping including Land Equivalent Ratio (LER), Actual Yield Loss (AYL) and Intercropping Advantage (IA) were used (Javanshir et al., 2000). Data were analyzed using SAS 9.1 software and the means were separated by the least significant difference test at 5% probability level.Results and DiscussionThe experimental results revealed that as the irrigation interval increased and drought stress intensified, there was a decrease in total fodder yield, total ash content, acid detergent fiber, dry matter digestibility, and the yield of protein and crude fiber in the fodder. Regarding the effect of intercropping on the qualitative characteristics of fodder, the findings indicated that an increase in the proportion of sorghum in the intercropping system led to a significant reduction in the share of leaves in the total sorghum biomass, water-soluble carbohydrates, acid detergent fiber, and fodder digestibility. The evaluation of the advantage of intercropping based on LER and AYL index showed that the intercropping of 75% corn with 25% sorghum in severe water shortage stress (irrigation after 250 mm evaporation) compared to other ratios intercropping had a higher superiority than the monoculture of the species.ConclusionIn general, the results of this experiment showed that the use of intercropping, especially under conditions of limited irrigation, can be a suitable solution to improve fodder production compared to pure cultivation.